Reducing Dependence on Non-Sharia Loans through Sharia Family Financial Education: A Participatory Action Research in Limbungan Baru Village - Febri Delmi Yetti (Abdimas Indonesian Journal, 2025)
The objective of this community service program is to improve family economic resilience by strengthening Islamic financial literacy and management practices, enabling families to reduce their dependence on non-Islamic loans and develop healthy and sustainable financial habits. This community service program utilizes a Participatory Action Research (PAR) design, positioning the community as the subject of change through a continuous cycle of reflection, action, and reflection to address family dependence on non-Islamic loans. The program was implemented in Limbungan Baru Village, involving 15 partner families through five PAR stages (To Know, To Understand, To Plan, To Act, and To Change) over four months. Data collection techniques included participant observation, focus group discussions (FGDs), interviews, and documentation. Data were analyzed qualitatively through data reduction, thematic categorization, and synthesis of meaning. Validity was strengthened through triangulation and member checking, while upholding participatory ethical principles. This community service program resulted in improved Islamic financial literacy among families, characterized by changes in understanding, attitudes, and financial management practices, particularly in recording, budgeting, and financial decision-making. Dependence on non-Sharia-compliant loans has begun to decline gradually as families are able to control spending and postpone consumer loans through more rational and equitable planning. Furthermore, the PAR process builds collective awareness and community solidarity in addressing economic challenges as a shared, not merely individual, problem. The program still faces limitations in the form of unstable family incomes and the relatively short duration of mentoring, resulting in behavioral changes that are not yet fully distributed and permanent.